La influencia de los medios de comunicación tradicionales en el posicionamiento del candidato alcalde de Loja, Franco Quezada en las elecciones seccionales 2023 - Erráez Veintimilla, Santiago Alexander (2024)
This study addresses a unique case in the 2023 sectional elections in Loja, where the mayoral candidate, Franco Quezada, obtained a decisive victory with more than 41,000 votes. The notable thing about his victory is that it was achieved without resorting to traditional media, an atypical strategy considering the regular presence of opinion programs and political debates in these media, especially during electoral campaigns. The main objective of the investigation was to analyze how Quezada achieved broad electoral support without the influence of traditional media. To do this, information was collected and analyzed from January 3 to February 3, 2023, using a mixed methodological approach. This approach included the collection of quantitative data through surveys administered to a segment of voters, as well as qualitative data obtained from interviews with political analysts, the mayor himself, and a review of relevant bibliographic sources. The results revealed that 70% of voters did not feel influenced by political propaganda in traditional media, and their voting intention was not modified by the information disseminated through these channels. This conclusion suggests a change in the dynamics of influence of traditional media on electoral decisions, a finding that provides a new perspective on the relationship between media, political propaganda and electoral behavior